1985
DOI: 10.1080/00913847.1985.11708904
|View full text |Cite
|
Sign up to set email alerts
|

Medical Complaints After a Marathon Run in Cool Weather

Abstract: In brief: Little information is available about medical complaints after marathons held in cool weather. To obtain such information medical records were maintained on every runner requesting medical attention after the Bostonfest Marathon on Oct 30, 1983. One hundred sixty-four (11.5%) of the runners finishing the race requested medical attention at the finish line. Men and women requested attention with equal frequency, but younger (20 to 30 years old) and faster (finishing in less than 3:00) runners sought m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 11 publications
0
8
0
2
Order By: Relevance
“…This terminology is still used today,5 6 13 14 often synonymously with EAMC. This is despite the fact that EAMC is known to occur in individuals exercising in moderate to cool temperatures,6 15 and exposure to extreme cold has also been associated with EAMC in swimmers 2. It has also been reported that the development of EAMC is not directly related to an increased core temperature 16.…”
mentioning
confidence: 99%
“…This terminology is still used today,5 6 13 14 often synonymously with EAMC. This is despite the fact that EAMC is known to occur in individuals exercising in moderate to cool temperatures,6 15 and exposure to extreme cold has also been associated with EAMC in swimmers 2. It has also been reported that the development of EAMC is not directly related to an increased core temperature 16.…”
mentioning
confidence: 99%
“…1 Cold injury frequency in military personnel is reported to range from 0.2 to 366 per 1000 exposures. [1][2][3][4][5][6] As the scope of physical activity participation broadens (eg, extreme sports, adventure racing) and environments with the potential for extreme weather conditions become more accessible, a review of cold injury physiology, prevention, recognition, treatment, and management is warranted. Clinicians practicing in settings or geographic regions that predispose individuals to cold injury must be aware of these risks and implement strategies to prevent cold injuries and to minimize them when they occur.…”
mentioning
confidence: 99%
“…Durante maratonas realizadas em temperaturas frias ou muito frias, os distúrbios mais comuns são hipotermia, exaustão e desidratação. As queixas mais comuns são astenia, calafrios, letargia, fala arrastada, tonteira, diarréia e sede 53,81 . Um corredor se queixar de frio ou calor nem sempre se associa com alterações da temperatura retal 67 .…”
Section: Hipotermiaunclassified
“…Um corredor se queixar de frio ou calor nem sempre se associa com alterações da temperatura retal 67 . A desidratação é comum em clima frio 53,81 . Os corredores devem tentar repor lí-quidos em uma taxa semelhante à das perdas pela urina e suor.…”
Section: Hipotermiaunclassified